Cadmium induces iron deficiency anemia through the suppression of iron transport in the duodenum. (10th October 2020) - Fujiwara, Yasuyuki; Lee, Jin-Yong; Banno, Hiroki; Imai, Shunji; Tokumoto, Maki; Hasegawa, Tatsuya; Seko, Yoshiyuki; Nagase, Hisamitsu; Satoh, Masahiko
Graphical abstract: Hypothesized model of the inhibitory effect of Cd on Fe transport. Highlights: Cadmium decreases serum iron concentrations in mice. Cadmium inhibits the expression of iron transport-related genes in the mouse duodenum. Cadmium decreases duodenum levels of divalent metal transporter 1 and ferroportin 1. Cadmium decreases the expression of iron transport-related factors in Caco-2 cells. Abstract: Cadmium (Cd) is an environmental contaminant that triggers toxic effects in various tissues such as the kidney, liver, and lung. Cd can also cause abnormal iron metabolism, leading to anemia. Iron homeostasis is regulated by intestinal absorption. However, whether Cd affects the iron absorption pathway is unclear. We aimed to elucidate the relationship between the intestinal iron transporter system and Cd-induced iron deficiency anemia. C57BL/6J female and male mice, 129/Sv female mice, and DBA/2 female mice were given a single oral dose of CdCl2 by gavage. After 3 or 24 h, Cd decreased serum iron concentrations and inhibited the expression of iron transport-related genes in the duodenum. In particular, Cd decreased the levels of divalent metal transporter 1 and ferroportin 1 in the duodenum. In addition, human colon carcinoma Caco-2 cells were treated with CdCl2 . After 72 h, Cd decreased the expression of iron transport-related factors in Caco-2 cells with a pattern similar to that seen in the murine duodenum. These findings suggest that Cd inhibits iron absorption through direct suppression of iron transport in duodenal enterocytes and contributes to abnormal iron metabolism.